Non-classical interstitial sites and anomalous diffusion mechanisms in hcp-titanium. (15th September 2019) - Scotti, Lucia; Warnken, Nils; Mottura, Alessandro
Abstract: It is well known that Fe, Co and Ni are characterised by abnormally fast diffusivity in the hcp phase of Ti ( α -Ti). Their diffusivity values are 10 5 times higher than self-diffusion data, which is atypical for vacancy-mediated diffusion yet too slow for interstitial diffusion. Also, addition of Fe, Co and Ni appears to accelerate the solvent diffusivity, with dramatic ramifications on a number of diffusion-controlled mechanisms. The fast diffusivity of these elements in α -Ti seems to be the result of their ability to dissolve both interstitially and substitutionally. In fact, while the majority of Fe, Co and Ni atoms sit substitutionally within the hcp lattice, a small concentration of these solute atoms can move very fast through interstitial sites, determining the high diffusion coefficient values. In this work, a combination of density functional theory and Kinetic Monte Carlo simulations is used to investigate possible migration processes for both solute and solvent atoms and their effect on the macroscopic diffusivity. We find that traditional classical interstitial sites are unsuitable for these solute atoms, and that alternative interstitial sites are instead preferred. Calculations confirm that the fast diffusivity of these solute atoms is a result of their ability to diffuse both interstitially and by vacancy-mediated mechanisms, yielding excellent agreement with experimental values. It is possible for these solute atoms to swap position with solvent atoms without the presence of vacancies, leading to an accelerated solvent diffusion in the presence of relatively dilute levels of these solute elements. Graphical abstract: Image 1